An intimate loneliness : supporting bereaved parents and siblings - Riches, Gordon (Facing death., 2000)
"An Intimate Loneliness explores how family members attempt to come to terms with the death of an offspring or brother or sister. Drawing on relevant research and the authors' own experience of working with bereaved parents and siblings, this book examines the importance of social relationships in helping them adjust to their bereavement. This book considers the impact of bereavement on self and family identity. In particular, it examines the role of shared remembering in transforming survivors' relationships with the deceased, and in helping rebuild their own identity with a significantly changed family structure.".